2005
DOI: 10.1161/circulationaha.104.504340
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Number of Circulating Endothelial Progenitor Cells Predicts Future Cardiovascular Events

Abstract: Background— The maintenance of endothelial integrity plays a critical role in preventing atherosclerotic disease progression. Endothelial progenitor cells (EPCs) were experimentally shown to incorporate into sites of neovascularization and home to sites of endothelial denudation. Circulating EPCs may thus provide an endogenous repair mechanism to counteract ongoing risk factor–induced endothelial injury and to replace dysfunctional endothelium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
701
3
20

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,022 publications
(751 citation statements)
references
References 39 publications
27
701
3
20
Order By: Relevance
“…3 Furthermore, reduced circulating EPCs are associated with an increased risk of cardiovascular events. 4,5 Recent studies 6 have shown that the number of CD34 þ cells are lower in patients with stroke. However, the association between CD34 þ cells and the extent of carotid atherosclerosis has not been established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Furthermore, reduced circulating EPCs are associated with an increased risk of cardiovascular events. 4,5 Recent studies 6 have shown that the number of CD34 þ cells are lower in patients with stroke. However, the association between CD34 þ cells and the extent of carotid atherosclerosis has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…3 Furthermore, high circulating levels of EPCs, characterized by combined expression of CD34 and kinase insert domain receptor (KDR; CD34 þ /KDR þ ), are associated with reduced cardiovascular events, suggesting a protective effect of EPCs on progression of atherosclerotic diseases. 4,5 Recent studies have also shown that the circulating CD34 þ cells are significantly reduced in patients with stroke as compared with controls. 6 However, it remains unclear whether the reduced level of circulating EPCs contribute to the occurrence of cerebrovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the level of circulating EPCs (cEPCs) not only correlates with cumulative cardiovascular risk 6 and vascular function 7 but also predicts future cardiovascular events and atherosclerotic disease progression in patients with coronary artery disease (CAD). 8,9 Recently, advanced stages of heart failure were shown to be associated with reduced levels of cEPCs. 10 One study showed ICM was associated with selective impairment of progenitor cell function in the bone marrow and in the peripheral blood.…”
Section: Introductionmentioning
confidence: 99%
“…It follows that the number of circulating EPCs may reflect the "vascular health" of an individual, and thus represent a marker by which to assess cardiovascular disease risk. However, the lack of a uniform EPC definition complicates cross-study comparisons and may contribute to the apparent paradox of some studies that suggest that EPCs are reduced in the presence of cardiovascular risk factors and coronary artery disease (CAD) (Vasa et al 2001;Hill et al 2003;Schmidt-Lucke et al 2005), whereas others suggest that numbers are increased in those with obstructive CAD (George et al 2004;Massa et al 2005;Güven et al 2006).…”
mentioning
confidence: 99%
“…More importantly, there are data indicating that the vast majority of EPCs actually arise from the CD14 + subpopulation of peripheral blood mononuclear cells (PBMCs) (Rehman et al 2003;Gulati et al 2003;Romagnani et al 2005). However, previous studies focusing on the relationship between either CAD or cardiovascular risk factors and the level of EPCs either did not distinguish between the two types of EPCs (Vasa et al 2001;Hill et al 2003;George et al 2004) or studied only CD34 + -EPCs (Schmidt-Lucke et al 2005;Massa et al 2005). Therefore, the question of whether the level of CD14 + -EPCs correlates with either CAD or cardiovascular risks remains unresolved.…”
mentioning
confidence: 99%